LIVER CIRROCHIS MALIGNANT DEGENERATION : CASE REPORT - Nyoman Gede Bimantara (E-Jurnal Medika Udayana, 2014)
Liver cirrhosis is a chronic liver disease characterized by irreversible fibrosis , lobularstructure and vascular disorganization , as well as regenerative nodules of hepat ocytes ,which is the end result of hepatocellular damage . More than 40 % of asymptomaticpatients with cirrhosis . In this state of cirrhosis found time routine health examinationor at the time of autopsy . Liver cirrhosis can be caused by many things . The causesinclude infectious diseases , hereditary and metabolic diseases , drugs and toxins . Inwestern countries the most common cause of liver cirrhosis is alcohol consumption ,whereas in Indonesia is mainly caused by hepatitis B or C. The etiology of livercirrhosis affects the handling of this disease . Therapy was conducted aiming to reducethe progression of the disease , avoid ingredients that can add to liver damage ,prevention and treatment of complications . Treatment of liver cirrhosis requiringmedical teamwork , patients , and families and the environment in the management ofthis disease .